Characterisation of Patients with Systemic Lupus Erythematosus in Malta: A Population Based Cohort Cross-Sectional Study. (30th September 2018) - Magro, Rosalie; Borg, Andrew A.
Abstract : Systemic Lupus Erythematosus (SLE) is a multisystemic autoimmune disorder. The aim of this study was to characterise the SLE patients living in Malta in order to estimate the prevalence and incidence of SLE and characterise the clinical presentation as well as identify any unmet needs. 107 SLE patients who fulfilled SLICC classification criteria were identified. These were invited to participate in the study by means of an interview, blood and urine tests, and filling of the following questionnaires: Fatigue Severity Scale (FSS), visual analogue scale (VAS) for fatigue, Hospital Anxiety and Depression Scale (HADS), VAS for pain, Pittsburgh Sleep Quality Index (PSQI), and modified Health Assessment Questionnaire (mHAQ). The estimated prevalence of SLE in Malta is 29.3 patients per 100, 000 and the estimated incidence is 1.48 per 100, 000 per year. 93.5% of SLE patients were female, and the mean age at diagnosis was 33.1 years. 60.8% were overweight or obese and body mass index (BMI) had a significant positive correlation with daily dose of prednisolone (R=0.177, p=0.046). 20.7% and 3.3% had a moderate and high disease activity, respectively, as measured by SLEDAI-2K. Disease activity had a significant positive correlation with functional disability measured by mHAQ (R=0.417, p<0.001). 56.5% had an abnormal level of fatigue (FSS >3.7) and 57.6% had a high level of anxiety (HADS ≥8). This study has identified a number of unmet needs of SLE patients, including obesity, uncontrolled disease activity, fatigue, and anxiety.